Implementasi Manajemen Pembelajaran Daring Berbantuan Platform Kahoot Terhadap Kepuasan Mahasiswa - Kadek Hengki Primayana (STAHN Mpu Kuturan Singaraja, 2021)
Online learning has become a model for mainstream learning interactions during the Covid-19 pandemic. Online distance learning is an effective way to tackle learning that allows teachers and students to interact in virtual classrooms that can be accessed anywhere and anytime. One of the learning alternatives that are popularly used today is virtual classes using the Kahoot platform. Learning using the Kahoot platform is very well used to increase student interest in learning. By using the Kahoot platform in online collaborative learning, it is possible to avoid learning alone, each member who is involved in collaborative online can utilize one another's resources and skills, this means that it makes it easier to get information from each member in it, evaluate ideas, monitor the work of one each other. Keywords: Online Learning, Kahoot, Student Satisfaction